Subcortical lesions impact confrontation naming in bilinguals with later age of acquisition: An exploratory study. Issue 2 (4th March 2023) - González, David Andrés; Soble, Jason R.; Bailey, K. Chase; Bain, Kathleen M.; Marceaux, Janice C.
Abstract: The bilingual experience is believed to impact brain development and, possibly, cognitive performance. Subcortical structures, including the striatum and white matter, are believed related to confrontation naming performance among bilingual individuals with later age of acquisition (AoA) and lower proficiency of a second language (L2). However, these findings are primarily derived from healthy adult samples, although there is clinical significance for the interpretation of naming performance. The present study examined whether striatal and white matter lesions were associated with naming tasks in clinic-referred bilingual veterans ( n  = 29) and whether L2 AoA moderated this relationship. Clinically rated lesions, without regard for AoA, were not consistently correlated with naming performance. Moderation models (lesion × AoA) were significant across naming tasks (i.e., naming scores were negatively correlated with striatal lesions with increasing AoA). Effect sizes were higher among striatal models as compared to white matter models. Results extend prior neuroimaging findings with healthy bilinguals that AoA moderates the relationship between subcortical lesions and naming performance in bilingual patients, and suggests that clinicians should consider specifics of bilingual experience when interpreting test scores.